Altered N-glycosylation modulates TgrB1- and TgrC1-mediated development but not allorecognition in Dictyostelium - Li, Cheng-Lin Frank (J Cell Sci, 2015)
Cell surface adhesion receptors play diverse functions in multicellular development. In Dictyostelium, two immunoglobulin-like adhesion proteins, TgrB1 and TgrC1, are essential components with dual roles in morphogenesis and allorecognition during development. TgrB1 and TgrC1 form a heterophilic adhesion complex during cell contact and mediate intercellular communication. The underlying signaling pathways, however, have not been characterized. Here, we report on a mutation that suppresses the tgrB–tgrC1-defective developmental arrest. The mutated gene alg9 encodes a putative mannosyl transferase that participates in N-linked protein glycosylation. We show that alteration in N-linked glycosylation, caused by an alg9 mutation with a plasmid insertion (alg9(ins)) or tunicamycin treatment, can partially suppress the developmental phenotypes caused by tgrC1 deletion or replacement with an incompatible allele. The alg9(ins) mutation also preferentially primed cells toward a stalk-cell fate. Despite its effect on development, we found that altered N-linked glycosylation had no discernable effect on TgrB1-TgrC1-mediated allorecognition. Our results show that N-linked protein glycosylation can modulate developmental processes without disturbing cell-cell recognition, suggesting that tgrB1 and tgrC1 have distinct effects in the two processes.